Application of Supply Chain Management in Sharia Commercial Banks Performance in Indonesia by Sharia Conformity and Profitability Index (SCnPI) Approach - Sri Wahyuni; Pujiharto Pujiharto (International Journal of Supply Chain Management, 2020)
Abstract- This study aims to measure the supply chain management (SCM) effects on the performance of Islamic Commercial Banks with an approach to the Sharia Conformity and Profitability Index (SCnPI). This research is descriptive quantitative research. The object of this study is Islamic banking which was listed on the Indonesia Stock Exchange in 2013-2018. Sampling using a purposive sampling method. Data obtained by means of documentation, and data needed in the form of annual reports Islamic commercial banks that have information to measure the independent variable. The results show that there is a trade-off between the Shariah compliance index and the profitability index of Sharia Commercial Banks in Indonesia for 2012-2017. The biggest trade-off occurred in Victoria Syariah banks, with a sharia compliance index of 0.84, the highest Shariah compliance index achieved by Bank Panin Syariah which was 0.91, and the lowest average Sharia compliance index occurred at Mega Syariah banks which was 0.63. Judging from the average profitability, the highest ratio is shown by Bank Panin Syariah, which is 6.38. In short, SCM is a meaningful tool for the banking firms or the organizational performance and various departmental heads are very much aware to SCM practices for the greater banking performance.